Incidence and prevalence of rheumatoid arthritis in Denmark from 1998 to 2018: a nationwide register-based study. (2nd November 2022) - Soussi, BG; Cordtz, RL; Kristensen, S; Bork, CS; Christensen, JH; Schmidt, EB; Torp-Pedersen, C; Prieto-Alhambra, D; Dreyer, L
Abstract : Objective: To investigate the incidence and prevalence of rheumatoid arthritis (RA) in the adult Danish population. Method: In this nationwide register-based cohort study, patients with incident RA between 1998 and the end of 2018 were identified using Danish administrative registries. The age- and sex-standardized incidence rate (IR), incidence proportion (IP), lifetime risk (LR), and point prevalence (PP) of RA were calculated. RA was defined as a first-time RA diagnosis registered in the Danish National Patient Registry combined with a redeemed prescription of a conventional synthetic disease-modifying anti-rheumatic drug in the following year. In addition, three different case definitions of RA were explored. Results: The overall age- and sex-standardized IR of RA from 1998 to 2018 was 35.5 [95% confidence interval (CI) 35.1–35.9] per 100 000 person-years while the IP was 35.2 (95% CI 34.8–35.5) per 100 000 individuals. The IR was two-fold higher for women than for men. The LR of RA ranged from 2.3% to 3.4% for women and from 1.1% to 1.5% for men, depending on the RA case definition used. The overall PP of RA was 0.6% (95% CI 0.5–0.6%) in 2018: 0.8% (95% CI 0.7–0.8%) for women and 0.3% (95% CI 0.3–0.4%) for men. The prevalence increased about 1.5-fold from 2000 to 2018. Conclusion: The IR and PP were approximately two-fold higher for women than for men. The prevalence of RA in Denmark increased significantly from 2000 to 2018. The RA case definition had more impact on the results than the choice of denominator.